2022
DOI: 10.3390/md20120779
|View full text |Cite
|
Sign up to set email alerts
|

Dieckol Isolated from Eisenia bicyclis Ameliorates Wrinkling and Improves Skin Hydration via MAPK/AP-1 and TGF-β/Smad Signaling Pathways in UVB-Irradiated Hairless Mice

Abstract: Repetitive exposure to ultraviolet B (UVB) is one of the main causes of skin photoaging. We previously reported that dieckol isolated from Eisenia bicyclis extract has potential anti-photoaging effects in UVB-irradiated Hs68 cells. Here, we aimed to evaluate the anti-photoaging activity of dieckol in a UVB-irradiated hairless mouse model. In this study, hairless mice were exposed to UVB for eight weeks. At the same time, dieckol at two doses (5 or 10 mg/kg) was administered orally three times a week. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Photoaging is characterized by a loss of skin elasticity with the depletion of collagen, elastin, and hyaluronan content, resulting in coarse wrinkling and dysregulated pigmentation [1][2][3][4][5][6][7][8]. In the present study, UVA/UVB irradiation was used to mimic the exposure close to the solar spectrum that is mostly associated with skin photoaging induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photoaging is characterized by a loss of skin elasticity with the depletion of collagen, elastin, and hyaluronan content, resulting in coarse wrinkling and dysregulated pigmentation [1][2][3][4][5][6][7][8]. In the present study, UVA/UVB irradiation was used to mimic the exposure close to the solar spectrum that is mostly associated with skin photoaging induction.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the data from the gene expression analysis suggest that both MYC and CAL modulate signaling pathways related to the UVR-induced photodamage response. The Wnt/β-catennin signaling governs cell proliferation, migration, and cellular regeneration following UVR-induced skin damage [7,8,10]. The gene expression data indicated that MYC, but not HRE or CAL, positively regulated the mRNA expression of WNT5a and CTNNB1.…”
Section: Myconoside and Calceolarioside E From H Rhodopensis Modulate...mentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic exposure to UVB often induces an inflammatory response, resulting in the upregulated expression of proinflammatory cytokines, such as IL-1, IL-6 and TNF-α in the skin, contributing to the development of skin photoaging. 41 The excessive ROS produced by UVB exposure induces cellular oxidative stress, 42 leading to inflammatory damage, and accelerates photoaging of the skin by regulating the expression of certain key genes. In this study, we observed that RPalm, RP, HPR and ROL functioned to simultaneously and significantly alleviate UVB-irradiation induced inflammation and oxidative stress, revealing important molecular mechanisms underlying these retinoids' anti-photoaging activity.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic exposure to UVB often induces an inflammatory response, resulting in the upregulated expression of proinflammatory cytokines, such as IL‐1, IL‐6 and TNF‐α in the skin, contributing to the development of skin photoaging 41 . The excessive ROS produced by UVB exposure induces cellular oxidative stress, 42 leading to inflammatory damage, and accelerates photoaging of the skin by regulating the expression of certain key genes.…”
Section: Discussionmentioning
confidence: 99%